EKSISTENSI DAN KOMPETENSI PUSTAKAWAN - Nurmalina Nurmalina (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2015)
Hearing the word "librarian" still a lot of people wonder, what is the librarian? Limitations of public knowledge about the librarian, gave birth to their hesitancy to declare the post of librarian as a profession. They found the librarian's job does not demand professionalism and can be done by anyone. There is even a lightly saying that librarians are just builders keep the book and lend it to the user.